2014
DOI: 10.1523/jneurosci.3235-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Neurons Excite Cortically Projecting Basal Forebrain GABAergic Neurons

Abstract: The basal forebrain (BF) plays an important role in the control of cortical activation and attention. Understanding the modulation of BF neuronal activity is a prerequisite to treat disorders of cortical activation involving BF dysfunction, such as Alzheimer's disease. Here we reveal the interaction between cholinergic neurons and cortically projecting BF GABAergic neurons using immunohistochemistry and whole-cell recordings in vitro. In GAD67-GFP knock-in mice, BF cholinergic (choline acetyltransferase-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 43 publications
12
75
0
Order By: Relevance
“…Atrophy of BF cholinergic neurons has been widely replicated both in this disease and in normal aging (48). Cholinergic neurons normally excite BF GABA/PV neurons (41), and loss of BF GABA/PV neurons has been noted in aged mice which have accumulation of extracellular amyloid plaques and episodic-like memory impairments (49). Thus, reduced activity caused by the loss of cholinergic neurons or the direct loss of BF GABA/PV neurons may be partially responsible for cortical oscillation abnormalities and associated cognitive impairments in aging and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Atrophy of BF cholinergic neurons has been widely replicated both in this disease and in normal aging (48). Cholinergic neurons normally excite BF GABA/PV neurons (41), and loss of BF GABA/PV neurons has been noted in aged mice which have accumulation of extracellular amyloid plaques and episodic-like memory impairments (49). Thus, reduced activity caused by the loss of cholinergic neurons or the direct loss of BF GABA/PV neurons may be partially responsible for cortical oscillation abnormalities and associated cognitive impairments in aging and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 97%
“…Here, we found that saporin lesions of BF cholinergic neurons, resulting in a 70% loss of this cell type, did not significantly affect the ability of BF PV stimulation to induce a cortical 40-Hz response, suggesting that cholinergic neurons are not required. However, under normal conditions, cholinergic and GABA/PV neurons likely work together to control cortical activation and GBO activity because cholinergic neurons strongly excite identified BF GABA and PV neurons in vitro (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus both anatomical and functional substrates by which BF gamma oscillations could influence DMN cortical areas have been documented. However, parvalbumin GABAergic cells are depolarized by cholinergic activation (65), so that independent regulation of cholinergic and GABAergic projection networks requires additional mechanisms. It is thus possible that GABAergic and glutamatergic BF neurons cooperate to mediate the influence of the BF on the DMN.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have almost exclusively focused on recording the activity of single neurons, often labelled according to cell type, and linking their firing patterns to the cortical EEG (Duque et al, 2000;Manns et al, 2000aManns et al, , 2000bHassani et al, 2009), wake/sleep regulation (Szymusiak et al, 2000;Lee et al, 2004Lee et al, , 2005, aspects of sensory stimulation (Lin and Nicolelis, 2008;Nguyen and Lin, 2014), and behavioral task performance (Thomson et al, 2014;Tingley et al, 2014Tingley et al, , 2015. Convergent evidence (Zaborszky et al, 1999;Yang et al, 2014;Xu et al, 2015) indicates that BF contains multiple interconnected and heterogeneous networks, which operate as an ensemble to modulate cortical state and play distinct roles during sleep and wakefulness. It is thus quite surprising that very little is known about BF ensemble activity, as estimated by the LFP; but see (Quinn et al, 2010;Whitmore and Lin, 2016).…”
Section: Introductionmentioning
confidence: 99%